Application of artificial intelligence technology in CNC system. (16th March 2022) - Dong, Chunhui; Zhong, Cheng
The purpose of this paper is to study the application of artificial intelligence technology in CNC systems. The experimental results show that in the case of small samples, the reliability distribution model of CNC machine tools is not unique. The reliability model of CNC machine tools can be uniquely determined after the ANN model expansion data and the KS test method are used. There is a good balance between efficiency and convergence performance. Comparing the results of all the solution models, the relative mean square error of the 2-fold 3-parameter Weibull distribution after the expansion of the ANN model is the smallest, and its value is 0.0428, indicating that the method is feasible to solve the reliability distribution model of CNC machine tools and can produce more accurate results.